Image challenge: A diabetic man with facial swelling following recent Covid-19 infection. (January 2022) - Chowdhury, Melissa; Takata, Junko; Beegun, Issa; Burd, Chris; Tatla, Taranjit; Corrah, Tumena
Highlights: A 68-year-old man with COVID-19 infection presents with left sided facial swelling. Histology confirmed mucormycosis infection with Rhizopus species. Interdisciplinary input is crucial in this aggressive disease. Clinician vigilance is vital in the face of the ongoing pandemic. Abstract: A 68-year-old man with diabetes presented with shortness of breath, left sided facial swelling, and nasal discharge. He had recently returned from India and PCR was positive for SARS-CoV-2 Delta variant. CT head and diffusion-weighted MRI sinuses were performed and the patient underwent endoscopic sinus surgery before being transferred to a specialist skull base centre.